3D-printed polyurea-toughened Al2O3 cellular ceramic structures: Bioinspired dual-phase interpenetrating design for superior mechanical properties - Xueqin Zhang; Ruyue Su; Xiong Gao; Jingyi Chen; Rujie He (Journal of Advanced Ceramics)
Cellular ceramic structures (CCSs) are promising candidates for structural components because of their low density and superior load-bearing capacity. However, the brittleness and poor energy-absorbing ability of CCSs severely limit their applications. Inspired by composites in natural materials, whose stiff and tough constituents are arranged in a dual-phase interpenetrating architecture, we proposed a dual-phase interpenetrating architecture to achieve superior strength and toughness of CCSs simultaneously. Polyurea-toughened Al2O3 CCSs (P/CCSs) were fabricated via three-dimensional (3D) printing and infiltration. The effects of the structural configuration and relative density on the mechanical properties of P/CCSs under quasi-static and dynamic compressive loading were systematically discussed. It was demonstrated that polyurea effectively improved the mechanical properties of CCSs. The load-bearing capacity and energy-absorbing ability of P/CCSs under quasi-static compressive loading were 1.22–3.64 and 57–519 times those of CCSs. Additionally, the dynamic compressive strength and energy absorption of P/CCSs were 1.07–1.85 and 3.31–10.94 times those of CCSs. Furthermore, owing to the incorporation of polyurea, P/CCSs maintained structural integrity under large deformation, rather than undergoing catastrophic fracture. This work provides an effective solution to mitigate the adverse effects of ceramic brittleness, rendering P/CCSs promising candidates for structural components that require superior load-bearing capacity and energy-absorbing ability simultaneously.